Enhanced photocatalytic activity of nZnO/n+Al:ZnO homojunction with an overlayer of Al2O3 nanoballs. (28th April 2022) - A, Surya Mary; Joseph, Julie Ann; Nair, Bindu G; Jacob, Rajani; Remillard, Stephen K; Rulison, Forest D; Shaji, Sadasivan; Philip, Rachel Reena
Abstract: This paper reports improvement in the degradation efficiency of ZnO for the organic dye methylene blue by constructing a homojunction of nZnO and n + Al doped ZnO with an overlayer of alumina nanoballs. The thin film junction is fabricated by the simple, cost-effective two stage electrochemical method of anodization followed by electrochemical doping at room temperature. Structural, optical, morphological and electrical analyses are done to elucidate the corresponding properties of each layer as well as of the junction. The compositional depth profile is obtained by the Rutherford backscattering technique. Valence band x-ray photoelectron spectroscopy in conjunction with optical data is used for designing the schematic of the junction formation. The rectification ratio of the thin film junction is determined to be ∼10 2 from voltage–current data.